Reversible High Capacity and Reaction Mechanism of Cr2(NCN)3 Negative Electrodes for Li‐Ion Batteries. Issue 3 (29th January 2020) - Arayamparambil, Jeethu Jiju; Chen, Kaixuan; Iadecola, Antonella; Mann, Markus; Qiao, Xianji; Fraisse, Bernard; Dronskowski, Richard; Stievano, Lorenzo; Sougrati, Moulay Tahar
Abstract : A detailed study of the electrochemical reaction mechanism between lithium and the trivalent transition‐metal carbodiimide Cr2 (NCN)3, which shows excellent performance as a negative electrode material in Li‐ion batteries, is conducted combining complementary operando analyses and state‐of‐the‐art density functional theory (DFT) calculations. As predicted by DFT, and evidenced by operando X‐ray diffraction and Cr K‐edge absorption spectroscopy, a two‐step reaction pathway involving two redox couples (Cr 3+ /Cr 2+ and Cr 2+ /Cr 0 ) and a concomitant formation of Cr metal nanoparticles is apparent, thus indicating that the conversion reaction of this carbodiimide upon lithiation occurs only after a preliminary intercalation step involving two Li per unit formula. This mechanism, evidenced for the first time in transition‐metal carbodiimides, is likely behind its outstanding electrochemical performance as Cr2 (NCN)3 can maintain more than 600 mAh g −1 for 900 cycles at a high rate of 2 C. Abstract : The electrochemical lithiation/delithiation mechanism of Cr2 (NCN)3, studied by complementary operando analyses and density functional theory (DFT) calculations, follows a two‐step reaction pathway, implying a typical conversion reaction preceded by a preliminary intercalation step. This mechanism, evidenced for the first time in transition‐metal carbodiimides, is likely behind its outstanding electrochemical cycling performance as a negative electrode in Li‐ion batteries.